2017
DOI: 10.1002/jssc.201700635
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of alcohols including diols and triols by HPLC with ultraviolet detection based on the formation of a copper(II) complex

Abstract: We developed a reversed-phase high-performance liquid chromatography method with ultraviolet detection using on-line complexation with Cu(II) ion for analysis of five alcohols including diols and triol (methanol, ethanol, 1,2-propanediol, 1,3-propanediol, and glycerol). The Cu(II) ion concentration in the mobile phase had a great influence on the peak areas of these alcohols, but not on their retention times. Column temperature (25-40°C) and pH of the mobile phase did not affect the separation of analytes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A high-performance liquid chromatography (HPLC) method for the determination of propane-1, 2-diol in spirits was proposed by Tanaka et al (2017). In this case, the Cu(II) ions of the mobile phase enable the determination of the substance via an UV-detector (at 250 nm) with a LOD of 0.1 mL/L.…”
Section: Methods Of Analysis In Foodmentioning
confidence: 99%
See 2 more Smart Citations
“…A high-performance liquid chromatography (HPLC) method for the determination of propane-1, 2-diol in spirits was proposed by Tanaka et al (2017). In this case, the Cu(II) ions of the mobile phase enable the determination of the substance via an UV-detector (at 250 nm) with a LOD of 0.1 mL/L.…”
Section: Methods Of Analysis In Foodmentioning
confidence: 99%
“…In the literature other methods for manufacturing of propane‐1,2‐diol are reported or proposed, based on a liquid‐phase high pressure reaction (600 atmospheres) of synthetic gas in the presence of a rhodium cluster complex (ASTDR, ), an hydrogenolysis of glycerol by using various catalysts like: copper, nickel or noble metals (Bozga et al., ), highly active copper/magnesia (magnesium oxide) catalysts (Pudi et al., ) or a copper/zinc/magnesia catalyst (Mondal et al., ), chromium oxide, or ruthenium or platinum/tungsten catalysts (Kutz et al., ), via fermentation of deoxy sugars (i.e. rhamnose) or other substrates by using Clostridia, Enterobacteriaceae or yeasts (Tanaka et al., ; Kutz et al. ()). …”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that amino acids injected in the HPLC system are readily complexed in the ow of the mobile phase, which contains a Cu(II) ion, and the complexes can be separated by reversed-phase HPLC and detected with a UV detector [18]. In our previous report, we used reversed-phase HPLC with the complexation with Cu(II) ion to determine the organic acids and alcohols [19,20]. Aliphatic carboxylic acids could also be selectively determined by ion chromatography with UV detection based on complexation with a Cu(II) ion [21].…”
Section: Introductionmentioning
confidence: 99%